Identifying Functional Cysteine Residues in the Mitochondria - Bak, Daniel W. (ACS Chem Biol, 2017)
The mitochondria are dynamic organelles that regulate oxidative metabolism and mediate cellular redox homeostasis. Proteins within the mitochondria are exposed to large fluxes in the surrounding redox environment. In particular, cysteine residues within mitochondrial proteins sense and respond to these redox changes through oxidative modifications of the cysteine thiol group. These oxidative modifications result in a loss in cysteine reactivity, which can be monitored using cysteine-reactive chemical probes and quantitative mass spectrometry (MS). Analysis of cell lysates treated with cysteine-reactive probes enable the identification of hundreds of cysteine residues, however, the mitochondrial proteome is poorly represented (<10% of identified peptides), due to the low abundance of mitochondrial proteins and suppression of mitochondrial peptide MS signals by highly abundant cytosolic peptides. Here, we apply a mitochondrial isolation and purification protocol to substantially increase coverage of the mitochondrial cysteine proteome. Over 1,500 cysteine residues from ~450 mitochondrial proteins were identified, thereby enabling interrogation of an unprecedented number of mitochondrial cysteines. Specifically, these mitochondrial cysteines were ranked by reactivity to identify hyper-reactive cysteines with potential catalytic and regulatory functional roles. Furthermore, analyses of mitochondria exposed to nitrosative stress revealed previously uncharacterized sites of protein S-nitrosation on mitochondrial proteins. Together, the mitochondrial cysteine enrichment strategy presented herein enables detailed characterization of protein modifications that occur within the mitochondria during (patho)physiological fluxes in the redox environment.